Effect of Extraction Parameters (Raw Material Particle Size, Volume of Solvent, and Time) on the Process Yield of Rice Bran Oil - Abdul Haris Mulyadi; Esti Setianingsih; Yeti Rusmiati Hasanah (Universitas Muhammadiyah Purwokerto, 2022)
Rice bran oil is the result of oil extraction from rice bran. Extraction solvent proccessing conducted using ethanol. Rice bran oil can be used as a consuming oil and materials for making cosmetics.This research aimed to find effect of rice bran size, ethanol volume, extraction time and its interaction toward yield of rice bran oil. This research include pure experimental study based on explorative factorial design to find the most influencing factors. The low level of rice bran size is 0.014 mm, beside the high level is 0.085 mm. The volume of ethanol that are used in this research, 250 ml as low level and 400 ml as high level. And then 120 minute as low level of extraction time whereas 240 minute as its high level. Data analysis of yield was done with Minitab software Release 16 with 95% level of confidence.The results show that the size of rice bran was dominant in determining the most influencing factors.